2012
DOI: 10.1111/j.1943-278x.2012.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Child/Adolescent Abuse and Suicidal Behavior: Are They Sex Related?

Abstract: The association between childhood and adolescent abuse and suicidal behavior, and the possible contribution of abuse to sex differences in non lethal suicidal behavior, was investigated. Data were extracted from the Israel-based component of the WHO World Mental Health Survey (Kessler & Utsun, 2008a). Increased risk for ideation, plan, and suicidal attempt were associated with childhood abuse, and increased risk for attempt was associated also with abuse at adolescence. No associations with sex or sex by abuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A dose–response pattern has been established between childhood adversities, such as financial strain or other family conflict, and an increased risk of physical, behavioural, mental, and social problems later in life [ 13 ]. In a sample of 4859 individuals drawn from a population register, childhood sexual abuse (CSA) was found have a three to five-fold increase of risk for both NSSI and suicidal behaviour [ 14 , 15 ], and cross-sectional studies based on retrospective data have suggested an association between CSA, psychological strain, and mental health problems such as depression later in life [ 16 , 17 ]. CSA victims also seem more likely to develop mental disorders [ 18 , 19 ] and delinquent and violent behaviours [ 20 ] than do victims of other forms of abuse and neglect.…”
Section: Introductionmentioning
confidence: 99%
“…A dose–response pattern has been established between childhood adversities, such as financial strain or other family conflict, and an increased risk of physical, behavioural, mental, and social problems later in life [ 13 ]. In a sample of 4859 individuals drawn from a population register, childhood sexual abuse (CSA) was found have a three to five-fold increase of risk for both NSSI and suicidal behaviour [ 14 , 15 ], and cross-sectional studies based on retrospective data have suggested an association between CSA, psychological strain, and mental health problems such as depression later in life [ 16 , 17 ]. CSA victims also seem more likely to develop mental disorders [ 18 , 19 ] and delinquent and violent behaviours [ 20 ] than do victims of other forms of abuse and neglect.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding, therefore, the major factors which underpin suicidality such as suicide attempts, thoughts and behaviors has been established as a global health and policy priority [World Health Organization (WHO), 2014]. Empirical research has shown strong links between several types of childhood maltreatment and adult suicidality among individuals in the community and those diagnosed with psychiatric disorders (Gal et al ., 2012; Kim et al ., 2013). Consistent with the empirical findings, contemporary theories of suicidality have emphasized the role of childhood maltreatment, such as sexual and physical abuse, in the development of suicidality.…”
mentioning
confidence: 99%
“…Likely, the latter figures are an underestimate of events. Epidemiologic studies have shown that child or adolescent abuse have significant impact on children [ 29 , 30 ] (e.g., externalizing behaviors, disruptive behavior, conduct and academic problems in school, depressive symptoms), and on adolescents (e.g., delinquent behavior, drug use, academic maladjustment, depression) [ 31 ]. In addition, there are late effects among adults, including: affective and anxiety disorders, suicide behavior, substance abuse disorders and even psychosis [ 32 35 ].…”
Section: Discussionmentioning
confidence: 99%